2005
DOI: 10.1142/s0129054105003674
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for the Constrained Longest Common Subsequence Problems

Abstract: Given strings S1, S2, and P, the constrained longest common subsequence problem for S1 and S2 with respect to P is to find a longest common subsequence lcs of S1 and S2 which contains P as a subsequence. We present an algorithm which improves the time complexity of the problem from the previously known O(rn2m2) to O(rnm) where r, n, and m are the lengths of P, S1, and S2, respectively. As a generalization of this, we extend the definition of the problem so that the lcs sought contains a subsequence whose edit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 6 publications
0
47
0
Order By: Relevance
“…This is achieved based on recent algorithms which take as input a regular expression of length r and convert it into an e-free NFA with O(r) states and O(r log 2 r) transitions (Hromkoviěc et al, 2001;Schnitger, 2006;Geffert, 2003). This yields an O(n 2 r 2 log 2 r) time and O(n 2 r 2 ) space complexities for the algorithm of Chung et al We note that this was not observed by Arslan and Egecioglu (2005) and Chung et al (2007b).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This is achieved based on recent algorithms which take as input a regular expression of length r and convert it into an e-free NFA with O(r) states and O(r log 2 r) transitions (Hromkoviěc et al, 2001;Schnitger, 2006;Geffert, 2003). This yields an O(n 2 r 2 log 2 r) time and O(n 2 r 2 ) space complexities for the algorithm of Chung et al We note that this was not observed by Arslan and Egecioglu (2005) and Chung et al (2007b).…”
Section: Resultsmentioning
confidence: 83%
“…Various extensions of the Smith-Waterman algorithm (Smith and Waterman, 1981) modify the alignment considerations according to a priori knowledge (Arslan and Egecioglu, 2005;Chen and Chao, 2009;Iliopoulos and Rahman, 2008;Peng and Ting, 2005;Tsai, 2003;Sunyaev et al, 2004;Gotthilf et al, 2008). One kind of a priori knowledge is about shared properties (patterns), which are expected to be preserved by the alignment.…”
Section: Introduction Smentioning
confidence: 99%
“…Various extensions of the Smith-Waterman algorithm (Smith and Waterman, 1981) modify the alignment considerations according to a priori knowledge (Arslan and Egecioglu, 2005;Chen and Chao, 2009;Iliopoulos and Rahman, 2008;Peng and Ting, 2005;Tsai, 2003;Sunyaev et al, 2004;Gotthilf et al, 2008). One kind of a priori knowledge is about shared properties (patterns), which are expected to be preserved by the alignment.…”
Section: Introduction Smentioning
confidence: 99%
“…Later, Chin et al [6] and independently, Arslan and Egecioglu [2,3] presented improved algorithms with O(pn 2 ) time and space complexity.…”
Section: Introductionmentioning
confidence: 99%